Microwave-assisted production of activated carbons from oil palm shell in the presence of CO2 or N2 for CO2 adsorption - Hoseinzadeh Hesas, R.; Arami-Niya, Arash; Wan Daud, W.M.A.; Sahu, J.N. (ELSEVIER SCIENCE INC, 2015)
Activated carbon (AC) was prepared from oil palm shell using different ratios of KOH as an activation agent and various microwave irradiation powers. To study the effects of physical agents, the impregnated precursors were activated under a flow of CO2 or N2. Maximum BET surface areas of 1196 and 1630m2/g were achieved in the presence of CO2 and N2, respectively. The textural properties of the samples with the highest surface areas were investigated using ultimate and proximate analyses, SEM and FTIR. The CO2 adsorption results suggest that the ACs are promising adsorbents for gas separation or storage applications.